2008
DOI: 10.1158/1535-7163.mct-07-2142
|View full text |Cite
|
Sign up to set email alerts
|

Methylseleninic acid synergizes with tamoxifen to induce caspase-mediated apoptosis in breast cancer cells

Abstract: Tamoxifen has efficacy as a breast cancer therapy and chemoprevention agent. However, toxicity and resistance to tamoxifen limit its clinical application. There is an urgent need to develop compounds that may be combined with tamoxifen to improve efficacy and overcome toxicity and resistance. We showed previously that the organoselenium compound methylseleninic acid (MSA) increased the growth-inhibitory effect of tamoxifen and reversed tamoxifen resistance in breast cancer cells. In this study, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…Our previous in vitro studies demonstrated synergy between tamoxifen and organic selenium compounds for growth inhibition and apoptosis induction in breast cancer cell lines [20]. The present study extends the finding of synergy between selenium and tamoxifen in vitro, to demonstrate similar synergy in vivo through measurement of breast tumor xenograft growth, apoptosis, angiogenesis and ER signaling.…”
Section: Introductionsupporting
confidence: 82%
“…Our previous in vitro studies demonstrated synergy between tamoxifen and organic selenium compounds for growth inhibition and apoptosis induction in breast cancer cell lines [20]. The present study extends the finding of synergy between selenium and tamoxifen in vitro, to demonstrate similar synergy in vivo through measurement of breast tumor xenograft growth, apoptosis, angiogenesis and ER signaling.…”
Section: Introductionsupporting
confidence: 82%
“…In addition to combinations of selenium with other chemopreventive agents, recent studies have shown that selenium compounds also enhanced the effects of radiation and chemotherapeutic agents on cancer cells. Results from ours and others suggest that Se may have the potential to enhance the efficacy of other chemopreventive or chemotherapeutic agents (4246). …”
Section: Discussionmentioning
confidence: 59%
“…Based on accumulating evidence suggesting activation of caspase-dependent apoptosis by tamoxifen [5], [22], [23], we examined the effects on caspases cleavage and expression by treatment of tamoxifen with or without risperidone. As shown in Figure 5, tamoxifen treatment induced pronounced cleavage of caspase 9, caspase 7, and caspase 3 (5.83±0.35-fold, 3.52±0.03-fold, and 1.95±0.13-fold to control, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cytostasis, induced by cell cycle arrest, is a condition that is poorly tolerated by any cell and must either be escaped or resolved by cellular death, hence the apoptotic activity of these primarily cytostatic agents [21]. It has been reported that tamoxifen-induced apoptosis involves cleavage of caspase 9, caspase 7, caspase 3, and poly-ADP-ribose polymerase (PARP) [5], [22], [23]. Anti-apoptotic protein Bcl-2 and pro-apoptotic protein Bax are also important effectors in the regulation of tamoxifen-induced cell death [5], [24].…”
Section: Introductionmentioning
confidence: 99%